Different results despite high homology: Comparative expression of human and murine DNase1 in Pichia pastoris - Jan-Ole Krischek; Hans Georg Mannherz; Markus Napirei (PLoS ONE, 2025)
The prolonged persistence of extracellular chromatin and DNA is a salient feature of diseases like cystic fibrosis, systemic lupus erythematosus and COVID-19 associated microangiopathy. Since deoxyribonuclease I (DNase1) is a major endonuclease involved in DNA-related waste disposal, recombinant DNase1 is an important therapeutic biologic. Recently we described the production of recombinant murine DNase1 (rmDNase1) in Pichia pastoris by employing the α-mating factor prepro signal peptide (αMF-SP) a method, which we now applied to express recombinant human DNASE1 (rhDNASE1). In addition to an impaired cleavage of the αMF pro-peptide, which we also detected previously for mDNase1, expression of hDNASE1 resulted in a 70–80 times lower yield although both orthologues share a high structural and functional homology. Using mDNase1 expression as a guideline, we were able to increase the yield of hDNASE1 fourfold by optimizing parameters like nutrients, cultivation temperature, methanol supply, and codon usage. In addition, post-translational import into the rough endoplasmic reticulum (rER) was changed to co-translational import by employing the signal peptide (SP) of the α-subunit of the Oligosaccharyltransferase complex (Ost1) from Saccharomyces cerevisiae. These improvements resulted in the purification of ~ 8 mg pure mature rmDNase1 and ~ 0.4 mg rhDNASE1 per Liter expression medium of a culture with a cell density of OD600 =  40 in 24 hours. As a main cause for the expression difference, we assume varying folding abilities to reach a native conformation, which induce an elevated unproductive unfolded protein response within the rER during hDNASE1 expression. Concerning functionality, rhDNASE1 expressed in P. pastoris is comparable to Pulmozyme®, i.e. rhDNASE1 produced in Chinese hamster ovary (CHO) cells by Roche - Genentech. With respect to the biochemical effectivity, rmDNase1 is superior to rhDNASE1 due to its higher specific activity in the presence of Ca2 + /Mg2 + and the lower inhibition by monomeric actin.